Role of Motivation in Learning English Foreign Language on the Academic Achievements of Students in China - Yung, Leo (International Journal of Linguistics, 2023)
Purpose: The purpose of this study is to investigate the role of motivation in learning English foreign language on the academic achievements of students in China. Methodology: The study adopted a desktop methodology. Desk research refers to secondary data or that which can be collected without fieldwork. Desk research is basically involved in collecting data from existing resources hence it is often considered a low cost technique as compared to field research, as the main cost is involved in executive's time, telephone charges and directories. Thus, the study relied on already published studies, reports and statistics. This secondary data was easily accessed through the online journals and library. Findings: The findings revealed that there exists a contextual and methodological gap relating to the role of motivation in learning English foreign language on the academic achievements of students in China. Preliminary empirical review reveals that motivation is a component that is both very crucial and effective in the process of picking up a new language. Therefore, it is important for instructors and lecturers of languages to learn about, appreciate, and pay attention to the personalities of the pupils in their classes. In addition, they need to have an understanding of motivation, the significant value it holds, and the different forms it might take. Unique Contribution to Theory, Practice and Policy: The Gardner's Motivation theory, the Acculturation model and the Self Determination theory may be used to anchor future studies relating to the role of motivation in learning English foreign language. The study will be beneficial to EFL teachers and other relevant stakeholders in establishing policies and strategies to promote motivation in learning English foreign language.